2021
DOI: 10.1002/jhbp.871
|View full text |Cite|
|
Sign up to set email alerts
|

Assembling a library of typical surgery video clips to construct a system for assessing the surgical difficulty of laparoscopic cholecystectomy

Abstract: Background To explore best practices for acute cholecystitis, it is necessary to construct a system to assess the difficulty of laparoscopic cholecystectomy (LC) based on intraoperative findings. In this study, multiple evaluators assessed videos of LC to assemble a library of typical video clips for 25 intraoperative findings. Methods We have previously identified 25 items that contribute to surgical difficulty in LC. For each item, roughly 30‐second video clips were submitted from videos of LC performed at m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…1 “edematous changes,” was categorized as having “Fair” agreement. Regarding the previous study, “edematous changes” also revealed “Fair” agreement in the first round ( κ = 0.223, 90% CI: 0.096‐0.350; AC 1 = 0.314, 90% CI: 0.150‐0.479) 9 . Therefore, we adapted the definition of “edematous change” and added the description to the video clip.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…1 “edematous changes,” was categorized as having “Fair” agreement. Regarding the previous study, “edematous changes” also revealed “Fair” agreement in the first round ( κ = 0.223, 90% CI: 0.096‐0.350; AC 1 = 0.314, 90% CI: 0.150‐0.479) 9 . Therefore, we adapted the definition of “edematous change” and added the description to the video clip.…”
Section: Discussionmentioning
confidence: 92%
“…Regarding the previous study, "edematous changes" also revealed "Fair" agreement in the first round (κ = 0.223, 90% CI: 0.096-0.350; AC 1 = 0.314, 90% CI: 0.150-0.479). 9 Therefore, we adapted the definition of "edematous change" and added the description to the video clip. To further improve agreement, we added absence of "edematous change," in which abundant visceral adipose tissue mimics edema at the time of dissection, to the video clip library.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations